Financial Risk Management and Organizational Performance: A Systematic Literature Review - Muhammad Budi Utama; Adi Purmanto (Business Management, 2026)
Financial Risk Management (FRM) has evolved from a conventional financial control mechanism into a strategic capability that supports organizational resilience and long-term performance amid increasing economic, technological, and environmental uncertainty. This study aims to synthesize contemporary research on the relationship between Financial Risk Management and Organizational Performance through a Systematic Literature Review (SLR). The review followed the PRISMA 2020 guidelines and analyzed 42 peer-reviewed articles published between 2025 and 2026. Thematic synthesis identified six major research themes: Financial Risk Management, Artificial Intelligence and Risk Analytics, Climate Risk and Sustainability, Corporate Governance and ESG, Digital Transformation and Innovation, and Organizational Performance and Financial Resilience. The findings indicate that recent research increasingly adopts integrated approaches combining financial, technological, governance, and sustainability perspectives. Organizational performance is no longer measured solely by profitability but also by financial resilience, sustainability performance, market competitiveness, and innovation capability. Moreover, methodological trends reveal a transition from traditional econometric techniques toward machine learning, artificial intelligence, and advanced analytical models. This review proposes an integrated conceptual framework linking external environmental pressures, financial risk categories, strategic organizational capabilities, and multidimensional organizational performance. The study contributes by providing a comprehensive synthesis of recent literature and identifying future research directions toward integrated, technology-enabled, and sustainability-oriented Financial Risk Management.